Challenges and Opportunities in Urban Transport Projects : Career Reflections of Two World Bank Specialists - Kumar, Ajay; Zimmerman, Samuel (World Bank Group, Washington, DC, 2015)
Problems or even failure in transport initiatives are more likely for projects set in the urban areas of developing countries. Connecting a rural village to an all-weather road or restoring a section of national highway is usually straightforward. Costs are modest, institutional issues limited, and the benefits obvious. In contrast, urban transport is not a single mode governed by a single agency but a collection of modes with varied administrative boundaries and many private sector stakeholders. Successful urban transport strategies reflect an understanding of linkages among transport, land use, and environmental factors. Working out the complex local challenges requires social, political, and technical capacities often in short supply in developing countries. And even when a project manages to attain its physical objectives, the civil and governmental capacity needed for sustainability often remains underdeveloped. The institutional frictions and gaps point to the elements of the way forward on urban projects: thoroughly understand the local context, then build broad public consensus around the value of better transport and the value of institutional arrangements to sustain it.